CCNA Security (640-554) Portable Command Guide - Vachon, Bob (Cisco Press, 2012)
All the CCNA Security 640-554 commands in one compact, portable resource Preparing for the latest CCNA® Security exam? Here are all the CCNA Security commands you need in one condensed, portable resource. Filled with valuable, easy-to-access information, the CCNA Security Portable Command Guide is portable enough for you to use whether you're in the server room or the equipment closet. Completely updated to reflect the new CCNA Security 640-554 exam, this quick reference summarizes relevant Cisco IOS® Software commands, keywords, command arguments, and associated prompts, and offers tips and examples for applying these commands to real-world security challenges. Throughout, configuration examples provide an even deeper understanding of how to use IOS to protect networks. Topics covered include - Networking security fundamentals: concepts, policies, strategies, and more - Securing network infrastructure: network foundations, CCP, management plane and access, and data planes (IPv6/IPv4) - Secure connectivity: VPNs, cryptography, IPsec, and more - Threat control and containment: strategies, ACL threat mitigation, zone-based firewalls, and Cisco IOS IPS - Securing networks with ASA: ASDM, basic and advanced settings, and ASA SSL VPNs Bob Vachon is a professor at Cambrian College. He has held CCNP certification since 2002 and has collaborated on many Cisco Networking Academy courses. He was the lead author for the Academy's CCNA Security v1.1 curriculum that aligns to the Cisco IOS Network Security (IINS) certification exam (640-554). · Access all CCNA Security commands: use as a quick, offline resource for research and solutions · Logical how-to topic groupings provide one-stop research · Great for review before CCNA Security certification exams · Compact size makes it easy to carry with you, wherever you go · "Create Your Own Journal" section with blank, lined pages allows you to personalize the book for your needs · "What Do You Want to Do?" chart inside front cover helps you to quickly reference specific tasks This book is part of the Cisco Press® Certification Self-Study Product Family, which offers readers a self-paced study routine for Cisco® certification exams. Titles in the Cisco Press Certification Self-Study Product Family are part of a recommended learning program from Cisco that includes simulation and hands-on training from authorized Cisco Learning Partners and self-study products from Cisco Press.